2019
DOI: 10.1017/s1751731118001520
|View full text |Cite
|
Sign up to set email alerts
|

Dietary essential oils improve feed efficiency and hepatic antioxidant content of broiler chickens

Abstract: The aim of this study was to test the hypothesis of an improved growth, dietary nutrient availability and overall health of broiler chickens reared on recycled litter when fed a standardised combination of essential oils (EO; carvacrol, cinnamaldehyde and capsicum oleoresin). To assess the effect of dietary treatments, feed intake, weight gain, feed efficiency, availability of dietary nutrients and energy, villus morphometry, excreta sialic acid concentration, hepatic antioxidants and serum amyloid A (SAA) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Data tabulated in the database were subjected to a mixed [30] 450 0-21 oregano EOs 0-500 Tiihonen et al [51] 720 0-42 Blend (thy, cin) 0-20 Amad et al [9] 528 0-42 Blend (thy, ane) 0-750 Amerah et al [59] 192 0-35 Blend (cin, thy) 0-100 Alp et al [60] 1200 0-42 Oregano EOs 0-300 Bravo et al [61] 240 0-21 Blend (car, cin) 0-100 Bozkurt et al [62] 1248 [70] 310 0-21 Blend (cin, car) 0-100 Aristimunha et al [12] 930 0-42 Blend (thy, eug, pip) 0-300 Hafeez et al [71] 600 0-42 Blend (men, ane) 0-100 Basmacioğlu-Malayoğlu et al [10] 240 0-42 Blend (car, cum, eug) 0-300 Kim et al [6] 840 0-35 Blend (thy, ane) 0-150 Ding et al [72] 192 0-42 Star anise EOs (ane) 0-200 Masouri et al [33] 288 0-42 Khuzistanica EOs (car) 0-500 Mohiti-Asli and Ghanaatparast-Rashti [73] 200 0-42 Blend (oregano, anise and citrus peel) 0-500 Paraskeuas et al [74] 150 0-42 Blend (men, ane, eug) 0-150 Ri et al [75] 180 0-42 Oregano EOs 0-150 Altop et al [28] 375 0-42 Sweet gum EOs 0-162.2 Giannenas et al [76] 320 0-42 Blend (β-car, men) 0-500 Hosseini and Meimandipour [77] 150 0-42 Thyme EOs 0-80 Mohiti-Asli and Ghanaatparast-Rashti [78] 200 0-42 Blend (oregano, anise and citrus peel) and oregano 0-500 Pirgozliev et al [7] 256 0-21 Blend (cin, car, cap) 0-100 Park and Kim [38] 360 0-42 Blend (thy, eug, pip) 0-300 Reis et al [52] 240 0-42 Blend (car, thy, cin) 0-500 Abdel-Wareth et al [25] 384 0-35 peppermint EOs and men 0-222 Attia et al [11] 216 0-36 Blend (cin, thy) 0-150 Galli et al [53] 135…”
Section: Discussionmentioning
confidence: 99%
“…Data tabulated in the database were subjected to a mixed [30] 450 0-21 oregano EOs 0-500 Tiihonen et al [51] 720 0-42 Blend (thy, cin) 0-20 Amad et al [9] 528 0-42 Blend (thy, ane) 0-750 Amerah et al [59] 192 0-35 Blend (cin, thy) 0-100 Alp et al [60] 1200 0-42 Oregano EOs 0-300 Bravo et al [61] 240 0-21 Blend (car, cin) 0-100 Bozkurt et al [62] 1248 [70] 310 0-21 Blend (cin, car) 0-100 Aristimunha et al [12] 930 0-42 Blend (thy, eug, pip) 0-300 Hafeez et al [71] 600 0-42 Blend (men, ane) 0-100 Basmacioğlu-Malayoğlu et al [10] 240 0-42 Blend (car, cum, eug) 0-300 Kim et al [6] 840 0-35 Blend (thy, ane) 0-150 Ding et al [72] 192 0-42 Star anise EOs (ane) 0-200 Masouri et al [33] 288 0-42 Khuzistanica EOs (car) 0-500 Mohiti-Asli and Ghanaatparast-Rashti [73] 200 0-42 Blend (oregano, anise and citrus peel) 0-500 Paraskeuas et al [74] 150 0-42 Blend (men, ane, eug) 0-150 Ri et al [75] 180 0-42 Oregano EOs 0-150 Altop et al [28] 375 0-42 Sweet gum EOs 0-162.2 Giannenas et al [76] 320 0-42 Blend (β-car, men) 0-500 Hosseini and Meimandipour [77] 150 0-42 Thyme EOs 0-80 Mohiti-Asli and Ghanaatparast-Rashti [78] 200 0-42 Blend (oregano, anise and citrus peel) and oregano 0-500 Pirgozliev et al [7] 256 0-21 Blend (cin, car, cap) 0-100 Park and Kim [38] 360 0-42 Blend (thy, eug, pip) 0-300 Reis et al [52] 240 0-42 Blend (car, thy, cin) 0-500 Abdel-Wareth et al [25] 384 0-35 peppermint EOs and men 0-222 Attia et al [11] 216 0-36 Blend (cin, thy) 0-150 Galli et al [53] 135…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils ( EOs ) have been used as a promising in-feed antibiotics alternatives due to their natural, low-toxicity, and no-residue properties ( Bassolé and Juliani, 2012 ). In vitro and in vivo trials have demonstrated that EOs exhibit different biological functions, including antioxidant status ( Chowdhury et al., 2018 ; Pirgozliev et al., 2019b ) and antibacterial, anti-inflammatory ( Liu et al., 2019 ), antiviral ( El-Shall et al. 2020 ), and antiparasitic activities ( Bozkurt et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine ( TCM ) has been regarded as an invaluable source of therapeutic agents and played an important role in maintaining both human and animal health ( Mishra and Tiwari, 2011 ). Some TCMs with low toxicity, like Galla Chinensis ( Xiang et al., 2015 ), Andrographis paniculata ( Worasuttayangkurn et al., 2019 ), Arctii Fructus ( Xu et al., 2015 ; Bok et al., 2017 ), Glycyrrhizae Radix ( Jiang et al., 2020a ), and Schizonepeta tenuifolia ( Fung and Lau, 2002 ), contain various active ingredients, such as terpenoids, phenols, and volatile oils, which can not only improve growth performance, immune function, and intestinal microbiota of livestock and poultry, but also have antioxidant and anti-inflammatory activities ( Samuel et al., 2017 ; Li et al., 2018 ; Pirgozliev et al., 2019 ; Jiang et al., 2020b ; Shi et al., 2020 ). Compared with antibiotics, TCMs have many advantages including less toxicity and side effects, and reduced residues in body and risk of inducing drug resistance ( Abdallah et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%